2010
DOI: 10.1007/s12350-009-9159-9
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and clinical benefit of combined coronary calcium and perfusion assessment in patients undergoing PET/CT myocardial perfusion stress imaging

Abstract: Subclinical CAD is common in patients without known CAD and normal myocardial perfusion assessed by hybrid PET/CT imaging. Identification of CAC influences subsequent physician prescribing patterns such that those with CAC are more likely to be treated with proven medical therapy for the treatment of CAD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…This score applies to any combination of ITPD and CAC values, in contrast to previously proposed CAC thresholds (6,25). Consequently, the developed technique allows us to demonstrate the increase in the overall diagnostic performance of hybrid PET/ CAC in consecutive patients referred to clinically indicated MPI for suspected CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This score applies to any combination of ITPD and CAC values, in contrast to previously proposed CAC thresholds (6,25). Consequently, the developed technique allows us to demonstrate the increase in the overall diagnostic performance of hybrid PET/ CAC in consecutive patients referred to clinically indicated MPI for suspected CAD.…”
Section: Discussionmentioning
confidence: 99%
“…PETmyocar dial perfusion imaging (MPI) is a well-established noninvasive procedure for the evaluation and risk stratification of patients with coronary artery disease (CAD) (1)(2)(3)(4)(5)(6)(7)(8). A principal advantage of hybrid PET combined with CT, compared with SPECT, is its potential ability to evaluate the coronary atherosclerotic burden as assessed by the coronary artery calcium (CAC) score during the PET scan.…”
mentioning
confidence: 99%
“…Limited data suggest that CAC influences physicians' management of CAD risk factors. 233 Although an exploratory subgroup analysis from a single randomized, clinical trial suggests that statin therapy in asymptomatic patients with CAC >400 may improve outcomes, 234 no dedicated, prospective studies have been performed to suggest that the detection of subclinical CAD by CAC leads to improvement in clinical events.…”
Section: Subclinical Cad Assessmentmentioning
confidence: 99%
“…4 The introduction of hybrid imaging as single photon emission computed tomography (SPECT)/computed tomography (CT) and positron emission tomography/CT allows to perform morphological and functional imaging in a same study session with a comfortable accuracy. 5 A combined evaluation of functional and structural abnormalities allows to improve the detection of obstructive CAD and to better stratify patients at low-intermediate risk of CAD. 6 Previous studies demonstrated that the major predictors of events in patients with suspected CAD are the extent of atherosclerotic burden, assessed by CAC, and the extent and severity of stress-induced myocardial ischemia, as assessed by MPI.…”
mentioning
confidence: 99%